The eloquence of the figure of speech between the linguistic meaning and the mystical meaning In the Divan of the Poet Omar Ibn Al-Farid - سليمان, بثينة; كورج , عيسى مصطفى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research seeks a conscious reading of the eloquence of the figure of speech between the linguistic meaning and the mystical meaning in the poetry of the poet Omar Ibn Al-Farid, These are artistic images that express the creations of himself, which attract the attention of the recipient to live within the poetic event depicted by the poet. It aims to highlight Ibn al-Farid’s poeticity in employing his expressive means of analogy, metaphor, metonymy, and others in an attempt by text towards openness to Sufi interpretation